KEPEMIMPINAN DAN KOMUNIKASI DAKWAH NABI SULAIMAN A.S DALAM PERSPEKTIF DAKWAH DIGITAL - Moh Syahri Sauma (An-Nida' : Jurnal Komunikasi dan Penyiaran Islam, 2024)
This paper explores the leadership and communication strategies employed by Prophet Sulaiman in the context of da'wah (Islamic propagation) and how they can be interpreted and applied within the framework of digital da'wah. Drawing from Islamic literature and contemporary understandings of digital communication, the study investigates the multifaceted approaches of Prophet Sulaiman in leading and communicating the message of Islam, examining their relevance and implications for digital da'wah in the modern age. Firstly, the paper delves into the leadership qualities demonstrated by Prophet Sulaiman, emphasizing his wisdom, justice, and strategic decision-making abilities. It highlights how these attributes enabled him to effectively govern and lead his people, establishing a just and prosperous society conducive to the propagation of Islamic teachings. Secondly, the communication strategies employed by Prophet Sulaiman are analyzed, focusing on his skillful utilization of language, diplomacy, and persuasion to convey the message of Islam to diverse audiences. His interactions with various stakeholders, including fellow monarchs, subjects, and supernatural beings, exemplify effective communication methods adaptable to the digital realm. Furthermore, the paper examines the relevance of Prophet Sulaiman's leadership and communication approaches in the context of digital da'wah. It explores how contemporary digital platforms such as social media, websites, and multimedia content can be leveraged to emulate Prophet Sulaiman's strategies, reaching a global audience and fostering engagement with Islamic teachings. The study underscores the importance of integrating principles of wisdom, justice, creativity, and humility into digital da'wah efforts, drawing inspiration from Prophet Sulaiman's exemplary leadership and communication style. By applying these principles in the digital sphere, contemporary da'wah practitioners can enhance their effectiveness in conveying the message of Islam, promoting understanding, and fostering positive engagement with diverse audiences worldwide.